Improving Health Outcomes in Coronary Artery Disease Patients with Short-Term Protocols of High-Intensity Interval Training and Moderate-Intensity Continuous Training: A Community-Based Randomized Controlled Trial - Catarina Gonçalves; Jorge Bravo; João Pais; Ana Abreu; Armando Raimundo (Hindawi-Wiley, 2023)
Studies have shown that the higher the aerobic capacity, the lower the risk of cardiovascular mortality and morbidity. In the case of cardiac patients, high-intensity interval training (HIIT) seems to be more effective than moderate-intensity continuous training (MICT) in improving aerobic capacity. The aim of this study was to investigate the effects of two community-based exercise programs using two short-term protocols (HIIT and MICT) on physical fitness and physical activity (PA) levels in coronary artery disease (CAD) patients. Methods. In this randomized controlled trial, body composition, aerobic capacity, muscle strength, and daily PA levels were assessed before and after 6 weeks of intervention in 69 patients diagnosed with CAD. All patients were randomly (1 : 1 : 1) assigned to two exercise groups (HIIT or MICT) or a control group (no exercise). Both training programs consisted of 6 weeks of supervised treadmill exercise, three sessions per week. MICT targeted ≈70-75% of peak heart rate (HR), while HIIT aimed for ≈85-95% of peak HR. The control group only followed the medical recommendations. Results. Community-based exercise programs showed more positive effects on physical fitness variables and physical activity levels compared to control. HIIT could significantly improve waist circumference, body fat mass, VO2peak, sedentary behavior, and moderate-to-vigorous PA compared to MICT. Moreover, the control group showed poorer results. Conclusion. HIIT can improve health outcomes more positively than MICT and control. These findings indicate that HIIT may be an alternative and effective training method in community-based exercise programs for CAD patients. This trial is registered with NCT03538119.